Silent reading and discussion of self-selected books in the contemporary classroom - Merga, Margaret (AATE, 2018)
Silent reading and book discussion about books read for pleasure can increase reading frequency and support the strengthening of student engagement in the beneficial practice of recreational reading. However, little is known about children’s attitudes toward and experiences of these pedagogical activities. Qualitative findings from 47 children aged eight to 11 across 24 elementary schools in Western Australia provide insight into this area of research. Silent reading is typically enjoyable, though dependent on the book, choice, access and reading environment, and it is vulnerable to inconsistent delivery. Very few children had the opportunity to discuss self-selected reading material in the classroom context, though the potential of this discussion for promoting a shared social experience and book recommendations was recognised. These mutually supportive strategies are best delivered separately, and greater consideration and value should be given to them, despite the current assessment-focused, high-stakes learning contexts of contemporary Australian schools.